2004
DOI: 10.1289/ehp.6756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organochlorine contaminants on thyroid hormone levels in Arctic breeding glaucous gulls, Larus hyperboreus.

Abstract: Studies on glaucous gulls (Larus hyperboreus) breeding in the Barents Sea have reported that high blood levels of halogenated organic contaminants in this species might cause reproductive, behavioral, and developmental stress. However, potential endocrine system modulation caused by contaminant exposure has yet not been reported in this Arctic apical predator. In this present study we aimed to investigate whether the current levels of a selection of organochlorines (OCs) were associated with altered circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 47 publications
5
56
4
Order By: Relevance
“…Confounding influences include gender [46]; correlative relationships with other compounds that occur in higher concentrations and also impact thyroid hormones [47]; and timing, insofar as hormones change over short time scales, and even small differences in sampling age could alter perceived relationships [42,48]. Methodological issues include whether free versus bound hormones are measured (Table 2; [50]) and whether plasma or thyroid gland T4 content is measured, with the latter suggested as a better measure of endocrine disruption [51].…”
Section: Contaminants and Thyroid Hormonesmentioning
confidence: 99%
“…Confounding influences include gender [46]; correlative relationships with other compounds that occur in higher concentrations and also impact thyroid hormones [47]; and timing, insofar as hormones change over short time scales, and even small differences in sampling age could alter perceived relationships [42,48]. Methodological issues include whether free versus bound hormones are measured (Table 2; [50]) and whether plasma or thyroid gland T4 content is measured, with the latter suggested as a better measure of endocrine disruption [51].…”
Section: Contaminants and Thyroid Hormonesmentioning
confidence: 99%
“…However, other studies found no measurable thyroid effects (94). Blubber concentration of DDT correlated negatively to TT3 and free T3 in seals (26, 27), whereas a study of sea-gulls showed no correlations with THs (95).…”
Section: Other Chemicalsmentioning
confidence: 91%
“…This indicated an increased peripheral T4 metabolism, which may represent local hypothyroidism in the fetal brain, where 5 0 DII is responsible for deiodination of T4 to the biologically active T3. Wildlife observations of HCB exposure showed negative correlations to the ratio TT4/FT4 in polar bears (25), and to T4 and T4/T3 ratio in gulls (95). A study of seals found no associations of THs to HCB (27).…”
Section: Other Chemicalsmentioning
confidence: 99%
“…All sample tests were done in duplicates. Readings with a coefficient of variation greater than 15% were excluded from the final data set [21].…”
Section: Thyroid Hormone Assaymentioning
confidence: 99%